Music as an art - Scruton, Roger (Bloomsbury Continuum, 2018)
Roger Scruton is a polymath. He has written authoritatively on a huge range of subjects from the environment to wine, from cosmology to the Middle East. He is also an accomplished musician (organ and piano) and a composer of works including an opera and a song cycle. This is Scruton's second major work on music for Bloomsbury--the first being Understanding Music (Continuum, 2009). In this new book he turns again to the meaning of tonality and sound. His abstract, somewhat mystical, argument on these topics includes slashing attacks on Marxist reductionism, the authenticity of Early Music, on rival aestheticians such as Adorno and on sentimentality and cliché in any form.